Impact of Oral Health on The Quality of Life of Elementary School Teachers (2015)
The success of preventive school health programs is largely dependent on teachers who are role models to pupils and pivotal to implementation. It is therefore important to understand the perception of school teachers about the impact of oral health on their daily activities. The aim of this study was to assess oral health related quality of life of elementary school teachers by evaluating the impact of oral conditions like dental caries and periodontal disease on their daily performances and school work. This was a descriptive cross sectional study in which 407 teachers were selected through multistage random sampling technique. Data were collected with structured interviewer-administered Oral Impact on Daily Performances (OIDP) questionnaires and by clinical oral examinations. Data were collated and analyzed with SPSS. The prevalence of reporting of impacts on daily performances was 39.1% with eating and enjoying food being the most commonly impacted activity. Impacts on daily performances were more likely to be reported by teachers with better education (p = 0.019). Teachers with caries had higher odds of reporting impacts as a result of oral health status (CI: 1.04, 5.64, p = 0.040). The severity of periodontal disease found on clinical examination was not related to reporting of impacts on quality of life (p > 0.05). The oral health status of school teachers impacted significantly on their daily performance and school work when they experienced pain. Painless but highly prevalent oral lesions were, however, not perceived to influence their quality of life